2005
DOI: 10.1590/s0100-29452005000300038
|View full text |Cite
|
Sign up to set email alerts
|

Indução de embriogênese somática em cupuaçu (Theobroma grandiflorum Schum.)

Abstract: RESUMO -Folhas jovens de cupuaçu (Theobroma grandiflorum Schum.) foram empregadas para indução de embriogênese somática, as quais foram cultivadas inicialmente em meio MS suplementado com 6,0 mg/L BAP e 0,5 mg/L AIA (meio de estabelecimento), seguindo-se o cultivo em meio MS suplementado com 2,20 mg/L TDZ (meio de indução). A região da nervura mostrou intumescimento três dias após inoculação no meio de estabelecimento, o qual foi seguido pela formação de cachos de calos. As massas calosas foram transferidas pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…The data presented here demonstrate that the reaction to acetocarmine was identical for both growth regulators; however, the 2,4-D-treated cells were less reactive to Evans blue, particularly at the concentration of 4.5 μM. According to Steiner et al (2005) and George et al (2008), a positive reaction to acetocarmine versus Evans blue identifies embryogenic cells. Thus, the J. curcas callus grown on 4.52 μM of 2,4-D exhibited a higher embryogenic potential.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…The data presented here demonstrate that the reaction to acetocarmine was identical for both growth regulators; however, the 2,4-D-treated cells were less reactive to Evans blue, particularly at the concentration of 4.5 μM. According to Steiner et al (2005) and George et al (2008), a positive reaction to acetocarmine versus Evans blue identifies embryogenic cells. Thus, the J. curcas callus grown on 4.52 μM of 2,4-D exhibited a higher embryogenic potential.…”
Section: Resultssupporting
confidence: 60%
“…The SEM analysis showed that the cell masses treated with 4.52 μM of 2,4-D were rounded and that structures similar to embryoid calogênica appeared between the surfaces (Figure 1 F and G). These structures were also observed by Ferreira et al (2005) to induce somatic embryogenesis in cupuaçu (Theobroma grandiflorum) under the effect of TDZ (Thidiazuron). The developmental stages of somatic embryos include globular, heart, torpedo and cotyledon stages.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations